2013
DOI: 10.4236/jep.2013.49111
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Organochlorine Pesticide Residues in the Buffalo Milk Samples of Delhi City, India

Abstract: The ill effects of green revolution include residues of extensively used chemical pesticides in various environmental components. The present study was designed to analyze the levels of organochlorine pesticide residues along with chemical composition in buffalo milk samples collected from different localities of Delhi. Milk monitoring can yield information about the kinds and quantities of pesticides in the environment as well as in our daily diet. In this study, the residue of three different organochlorine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
(38 reference statements)
6
16
1
Order By: Relevance
“…The residues of o,p' DDD of 0.002 ppm was reported by Panseri [12], which is far below than the MRL level (0.05 ppm) specified by EU (CE: 698: 2005). Residue levels of P'P'-DDT of 0.038 and 0.033 ppm were reported by Mohd Aslam [19] and Kampire et al [20] respectively. Donia [16] reported 0.022 ppm and 0.032 ppm in buffalo and cow milk respectively, whereas Waliszewski et al [21] reported residue levels of 0.0372 and 0.078 in mixed milk for p,p' DDT.…”
Section: Resultsmentioning
confidence: 99%
“…The residues of o,p' DDD of 0.002 ppm was reported by Panseri [12], which is far below than the MRL level (0.05 ppm) specified by EU (CE: 698: 2005). Residue levels of P'P'-DDT of 0.038 and 0.033 ppm were reported by Mohd Aslam [19] and Kampire et al [20] respectively. Donia [16] reported 0.022 ppm and 0.032 ppm in buffalo and cow milk respectively, whereas Waliszewski et al [21] reported residue levels of 0.0372 and 0.078 in mixed milk for p,p' DDT.…”
Section: Resultsmentioning
confidence: 99%
“…Of 72 samples analysed, 3 from South China contained higher levels of DDT and HCH residues that exceeded the FAO/WHO accepted tolerance level. Aslam et al (2013) reported pesticide Residue levels of P'P'-DDT of 0.038 and 0.033 ppm in buffalo milk samples of Delhi city, India .The gas chromatographic analysis of fodder samples of Zone 5 of Musi river showed the residues of dicofol at concentration of 0.07±0.0007 (0.071-0.077). Among organophosphorus compounds, dimetheoate was present in milk samples collected from Zone 6 at a level of 0.13±0.006 (0.111-0.167).…”
Section: Resultsmentioning
confidence: 99%
“…Shahzadi et al [10] quantified of organophosphorous (chlorpyrifos), pyrethroid (bifenthrin, deltamethrin and lambda cyhalothrin), insecticide (imidacloprid) and carbamate (carbofuran) pesticides in cow, buffalo, goat, camel and sheeps milk collected from different localities of Lahore, Pakistan. Aslam et al [12] found that 50% of the buffalo milk samples of Delhi, India were contaminated with organochlorine pesticides residues. Dallegrave et al [16] analyzed 17 different pyrethroids and chlorpyrifos in the fat content of animal products, including beef, chicken, eggs, fish, and milk.…”
Section: Discussionmentioning
confidence: 99%
“…This information is useful to assess potential health risks associated with the contribution of milk consumption for pesticides intake into the human either for babies or during the following age stages. So, determination of environmental chemicals in the common milk types are of broad scientific interest [12]. So this study aimed to investigate the residual levels of pesticides, including representing group of persistent organochlorine compounds beside certain pesticides of organophosphorous and pyrethroids (which are currently applied in agricultural practices) in milk of buffalo and human living in selected rural areas in Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation